The US and the Arab-Israeli conflict: a Palestinian perspective - Abu Arafeh, Abdel Rahman (2000)
With the end of the Gulf War and its aftermath, it became clear that the American administration would do something substantial for the interest of peace in the Middle East , in order to preserve its credibility after the split caused by the Arab parties that opposed the American position regarding the Gulf crisis. After decades of American diplomatic efforts, the administration accelerated its moves to bring all parties of the Middle East conflict to sit at one table. The United States exerted big efforts in arranging the Madrid conference by finding means to insure participation by all parties or by mobilizing support from concerned international powers, particularly Russia and the European Community. (Párrafo extraído del texto a modo de resumen)